On the vertical and horizontal profiles of the atmospheric electric field during thunderstorms. Issue 1 (1st December 2022) - Chilingarian, A; Hovsepyan, G; Karapetyan, T; Sargsyan, B; Zazyan, M
Abstract: We present the first results of a new experiment on Mt. Aragats for measuring the horizontal profile of atmospheric electric fields during thunderstorms. Networks of advanced particle spectrometers operated on the slopes of Mt. Aragats continuously measure fluxes of charged and neutral particles, periodically registering impulsive enhancements, so-called Thunderstorm Ground Enhancements (TGEs). This gives the possibility to estimate the strength of the electric field in the lower atmosphere. Relativistic Runaway Electron Avalanches (RREAs) are registered by the particle detectors located on the Earth's surface as TGEs sometimes exceeding the fair-weather fluxes up to a hundred times. The strong accelerating electric field can reach 1.7-2.2 kV/cm at altitudes 3-6 km, and extend down to 50-150 m above the Earth's surface. The horizontal extent of the electric field can reach 10 km and more.